The Attitudes of Students towards General Studies courses at the Afe Babalola University, Ado-Ekiti - Ojo, Olayinka Olabimpe; Abibu, Akinyemi Atinuke (Àgídìgbo: ABUAD Journal of the Humanities, 2013)
Students' attitude towards subjects influences the participation rate of learners. This study is a survey of students of Afe Babalola University, Ado-Ekiti to determine their attitude towards General Studies Courses (GST). Students of both genders constitute the population of this study. Sample of the study was 187 students (male=90 and female=97). The research instrument used was questionnaire structured in two sections. The analyses were done with both descriptive and inferential statistics, all were tested at p=0.05 level of sib •• ificance. Findings showed that class size will significantly influence the attitude of students towards GST courses; the Null hypothesis was thus rejected. Also, the study shows that there is no significant difference in the attitude of male and female students towards GST courses .Based on the findings, it was recommended that the class size needs to be reduced for more effective results in terms of student learning.